2019
DOI: 10.1055/s-0039-1694762
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Facial Lipofilling from a Historical Point of View

Abstract: Lipofilling, the transplantation of adipose tissue, has already been used since the end of the 19th century. For decades, lipofilling was used to restore loss of volume due to aging, trauma, or congenital defects. Later on, the indications for the use of lipofilling expanded by treating aged skin, scars, and improving wound healing. The expansion was caused by the discovery of adipose derived stromal cells (ASCs) in adipose tissue and the development of very fine harvesting and injection cannulas which made it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 103 publications
(120 reference statements)
0
8
0
Order By: Relevance
“…In these studies, however, cSVF is obtained enzymatically by time-consuming isolation procedures. These enzymatic procedures disrupt all cell–cell interactions including ECM [ 48 ]. Although several studies reported on the therapeutic effect of cSVF on osteoarthritis, the regenerative role of ECM is often underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, however, cSVF is obtained enzymatically by time-consuming isolation procedures. These enzymatic procedures disrupt all cell–cell interactions including ECM [ 48 ]. Although several studies reported on the therapeutic effect of cSVF on osteoarthritis, the regenerative role of ECM is often underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…However it is not always feasible. 18 Moreover, there is an increased risk of patient dissatisfaction in revision surgeries. This may be due to a change in the nasal anatomy, the development of scar tissue, the loss of cartilaginous support, the altered blood supply, and the compromised soft tissue envelope.…”
Section: Discussionmentioning
confidence: 99%
“…These results are ensured by ADCSs that promote angiogenesis and improve scar healing 17 . However, there is a controversy whether the effect of ADSCs is assured by their multi‐lineage differentiation ability or by the secretions of paracrine factors, exosomes, and cytokines that stimulate skin regeneration 18 . As a result, this treatment can be geared for cosmetic purposes and skin disorders such as radiation dermatitis and chronic ulceration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat grafting, also called lipofilling, has been applied for over 100 years since Neuber reported the first successful fat grafting procedure in 1893 (van Dongen, van Boxtel, Harmsen, & Stevens, 2019).…”
Section: Historymentioning
confidence: 99%